Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Hasil Belajar Siswa Pada Subtema 1 Energi dan Perubahannya Kelas III SD Negeri Percontohan Pematang Siantar - Dian Anggreni Tamba; Lisbet Novianti Sihombing; Desi Sijabat (Journal on Education, 2023)
The purpose of this study was to determine the effect of the Problem Based Learning (PBL) Learning Model on Student Learning Outcomes in Theme 6 Energy and Its Changes Sub-theme 1 Energy Sources Learning 1 Class III SD Negeri Pilotan, Pematang Siantar. Quantitative research with the type of Pre-Experimental Design with a research design One Group Pretest-Postest (Initial Test-Final Test in a single group). In this study using only one research class. The research sample was class III, totaling 31 students. The sampling technique of saturated sampling is a sampling technique when the population is used as the sample. Based on the results of data analysis and hypothesis testing that has been done, that the effect of the PBL learning model on student learning outcomes. greater than ttable (16.67> 2.045) then H0 is rejected and Ha is accepted. So it can be concluded that the PBL learning model has an effect on student outcomes in class III sub-theme 1 of the Pematangsiantar Pilot Public Elementary School.